Remote monitoring of patients with rheumatoid arthritis in a low disease activity state: a mixed methods evaluation across six hospitals in London, UK - Watson, Kathryn; Sheldon, Helen; Pallari, Elena; Arumalla, Nikita; Olive, Rachel R; Boiko, Olga; Aznar, Camille; Adams, Emma-Jayne; Bosworth, Ailsa; Demetriou, Len; Martin, Melanie; Palmer, Mary-Ann; et al. (Rheumatology (Oxford, England), 2024)
Objectives This study evaluated the scale-up of a remote monitoring service, capturing monthly Rheumatoid Arthritis Impact of Disease scores and patient-generated text messages, for patients with rheumatoid arthritis (RA; in remission or with low disease activity) attending routine outpatient clinics across six hospitals. We explored patients and staff experiences and implementation outcomes. Methods A pragmatic, mixed methods approach was used, with active patient involvement throughout. We undertook a rapid review, analysed service-level data, and conducted a patient survey and patient and staff interviews, informed by the Capability, Opportunity, Motivation, Behaviour (COM-B) and Exploration, Preparation, Implementation, Sustainment (EPIS) theoretical frameworks. Results The review included 37 articles, covering themes of patient and clinician acceptability, engagement, feasibility and clinical impact. Service-level data (n = 202) showed high levels of patient engagement with the service. The patient survey (n = 155) showed patients felt the service was easy to use, had confidence in it and felt it improved access to care. Patient interview (n = 22) findings mirrored those of the survey. Motivating factors included increased responsiveness and ease of contact with clinical teams. Views from staff interviews (n = 16) were more mixed. Some implementation barriers were specific to roll-out sites. Prioritization of staff needs was emphasized. Conclusion Patients were positive about the service and engagement was high. Staff views and engagement were more mixed. Results suggest that equal levels of patient and staff engagement are required for sustainability. These findings further our understanding of the implementation challenges to scaling remote monitoring interventions for patients with rheumatoid arthritis in routine care settings.